The making and unmaking of an industrial working class sliding down the labour hierarchy in Ahmedabad, India - Breman, Jan. (New Delhi New York Oxford University Press, 2004)
Study of the textile workers of Ahmedabad, India.
Includes bibliographical references and index.
Tac-1969g donated by UPAA Netherlands on 20 January 2015.
Keywords: Textile workers -- India -- Ahmedabad -- Economic conditions; Textile workers -- India -- Ahmedabad -- Social conditions; Textile industry -- India -- Ahmedabad -- History